Analisis Kesulitan Pemahaman Konsep pada Siswa di Madrasah Ibtida’iyah - Farich Purwantoro; Nur Fitri Amalia (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The purpose of this study is to identify the forms of difficulties experienced by students in understanding the concepts of the IPAS subject at Madrasah Ibtida’iyah, analyze the factors that cause these difficulties, and explain the impact of learning difficulties on students’ academic performance in the subject. The study also aims to explore the reasons behind students' struggles in learning. This research was conducted in Grade V at MI Raudlatul Hasan Condong. The study employed a mixed-methods approach, combining both quantitative and qualitative methods. Data collection instruments included pre-tests, observations, interviews, and documentation. Based on the data analysis, it was found that students’ learning difficulties in the IPAS subject were primarily caused by a lack of interest in the subject. This lack of interest had a direct impact on their academic performance, as evidenced by the test results: out of 51 students, 27 scored below the Minimum Mastery Criteria (KKM).